Identification of proteins and metabolic networks associated with sucrose accumulation in sugarcane (Saccharum spp. interspecific hybrids). Issue 1 (1st January 2021) - Qin, Cui-Xian; Chen, Zhong-Liang; Wang, Miao; Li, Ao-Mei; Liao, Fen; Li, Yang-Rui; Wang, Ming-Qiao; Long, Ming-Hua; Lakshmanan, Prakash; Huang, Dong-Liang
ABSTRACT: The rate of improvement of sugar content in sugarcane remains low for decades worldwide. Our previous transcriptome studies provided an atlas of sucrose accumulation-related gene expression, but little is known about the proteins involved. Here, we conducted a proteomic analysis of experimentally altered sucrose accumulation in sugarcane. Analysis of stem proteomes of sugarcane ripener ethephon treated high- and low-sugar genotypes had identified 2983 proteins of which 139 were significantly differentially expressed (DEPs). These DEPs were found to be associated with sugar metabolism-related processes with 25 of them may have a regulatory role in sucrose accumulation. The key proteins identified include UDP-glucose 6-dehydrogenase associated with amino sugar and nucleotide sugar metabolism; those involved in carbon fixation; and fructokinase, β-D-glucosidase, and α-glucan phosphorylase involved in starch and sucrose metabolism. Distinct genotype- and ethephon-dependent DEP expression was evident providing new insights into one of the most intractable sugarcane traits to breeding.